Planificación estratégica del sitio turístico Cascadas San Mateo, cantón las Naves-Provincia Bolívar, año 2022 - Aldaz Morales, Jessica Rosmery (2022)
Tourism as a dynamic source, is an important part of the country's productive sector generating employment and economic resources, in recent years tourism has stood out in Ecuador for showing its natural wealth and culture that it possesses in each of its provinces. The location of the "San Mateo Waterfalls" and the natural landscapes are attractions that have influenced tourists from other places to frequent them consecutively, becoming the favorite destination for many who prefer to get away from the outskirts of the city and look for a place of rest for them and their families, before this potential in development it is necessary that the authorities promote projects promoting tourism taking advantage of the internal strengths through natural tourism, organizing and planning effective tactics taking into account all the elements and promoting a responsible tourism of vision inclusive where all communities are involved achieving sustainable development that improves the quality of life for its inhabitants.